Child and caregiver involvement and shared decision-making during asthma pediatric visits - Sleath, Betsy (2011)
OBJECTIVE: The purpose of this study was to examine: (a) the extent to which caregivers and children asked asthma management questions during pediatric asthma visits, (b) the extent to which providers engaged in shared decision-making with these caregivers and children, and (c) the factors associated with question-asking and shared decision-making. METHODS: Children ages 8 through 16 with mild, moderate, or severe persistent asthma and their caregivers were recruited at five pediatric practices in non-urban areas of North Carolina. All of the medical visits were audio-tape recorded. Generalized estimating equations were used to analyze the data. RESULTS: Only 13% of children and 33% of caregivers asked one or more questions about asthma management. Caregivers were most likely to ask questions about their child’s medications. Providers obtained child input into their asthma management treatment plan during only 6% of encounters and caregiver input into their child’s asthma management treatment plan during 10% of visits. CONCLUSION: Given the importance of involving patients during health care visits, providers need to consider asking for and including child and caregiver input into asthma management treatment plans so that shared decision-making can occur more frequently.